AI-Powered HR: Ethical and Strategic Analysis of Artificial Intelligence Implementation in Recruitment Process in Indonesia - Falah, Zidnal; Syaifurrochman, Fajar; Anwar, Saeful; Anggraeni, Riska (Politeknik Siber Cerdika Internasional, 2025)
The development of artificial intelligence (AI) in the human resources (HR) sector, particularly in recruitment, is accelerating, including in Indonesia. The implementation of AI in the recruitment process offers great potential in terms of efficiency and reduction of human bias, but also raises ethical and strategic challenges. Therefore, it is important to understand how AI is applied in recruitment and its impact on the selection process and company decisions. This study aims to analyze the implementation of AI in the recruitment process in Indonesia, identify the ethical challenges that arise, and provide strategic recommendations for the effective and fair use of this technology. This study used a descriptive mixed-methods approach, which included in-depth interviews with HR managers and relevant staff as well as a survey of employees who have gone through AI-based recruitment. The data obtained was analyzed using thematic analysis techniques for qualitative data and descriptive statistics for quantitative data. The results show that although AI improves the efficiency of the recruitment process, many companies in Indonesia still face challenges related to the transparency of AI decisions and potential bias. Most companies use AI only in the early stages of selection, with the final decision still involving humans. The application of AI in recruitment in Indonesia can improve efficiency, but companies must pay more attention to ethics and transparency to ensure that this technology is used fairly. A hybrid approach that combines technology with human evaluation may be the best solution.